Overcoming roadblocks in the development of vaccines for leishmaniasis. (2nd November 2021) - Kaye, Paul M.; Mohan, Sakshi; Mantel, Carsten; Malhame, Melissa; Revill, Paul; Le Rutte, Epke; Parkash, Vivak; Layton, Alison M.; Lacey, Charles J.N.; Malvolti, Stefano
ABSTRACT: Introduction: The leishmaniases represent a group of parasitic diseases caused by infection with one of several species of Leishmania parasites. Disease presentation varies because of differences in parasite and host genetics and may be influenced by additional factors such as host nutritional status or co-infection. Studies in experimental models of Leishmania infection, vaccination of companion animals and human epidemiological data suggest that many forms of leishmaniasis could be prevented by vaccination, but no vaccines are currently available for human use. Areas covered: We describe some of the existing roadblocks to the development and implementation of an effective leishmaniasis vaccine, based on a review of recent literature found on PubMed, BioRxiv and MedRxiv. In addition to discussing scientific unknowns that hinder vaccine candidate identification and selection, we explore gaps in knowledge regarding the commercial and public health value propositions underpinning vaccine development and provide a route map for future research and advocacy. Expert opinion: Despite significant progress, leishmaniasis vaccine development remains hindered by significant gaps in understanding that span the vaccine development pipeline. Increased coordination and adoption of a more holistic view to vaccine development will be required to ensure more rapid progress in the years ahead.